TRPV4 regulates osteoblast differentiation and mitochondrial function that are relevant for channelopathy - Acharya, Tusar Kanta; Pal, Subhashis; Ghosh, Arijit; Kumar, Shamit; Kumar, Satish; Chattopadhyay, Naibedya; Goswami, Chandan (Frontiers in Cell and Developmental Biology, 2023)
Different ion channels present in the osteoblast regulate the cellular functions including bio-mineralization, a process that is a highly stochastic event. Cellular events and molecular signaling involved in such process is poorly understood. Here we demonstrate that TRPV4, a mechanosensitive ion channel is endogenously present in an osteoblast cell line (MC3T3-E1) and in primary osteoblasts. Pharmacological activation of TRPV4 enhanced intracellular Ca2+-level, expression of osteoblast-specific genes and caused increased bio-mineralization. TRPV4 activation also affects mitochondrial Ca2+-levels and mitochondrial metabolisms. We further demonstrate that different point mutants of TRPV4 induce different mitochondrial morphology and have different levels of mitochondrial translocation, collectively suggesting that TRPV4-mutation-induced bone disorders and other channelopathies are mostly due to mitochondrial abnormalities. These findings may have broad biomedical implications.